A Strategi Optimalisasi Saham - Saham Dengan Pendekatan Metode Indeks Tunggal Pada Perusahaan Tambang yang Terdaftar dalam LQ45 di BEI Periode 2020 – 2022 - Sari, Ananta Kumala; Bianca, Sullicyanna Luna; Permata Dinda, Bahiira Albasitha; R. Pandin, Maria Yovita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The purpose of this study is to determine the optimization strategy with a single index approach in mining companies included in LQ45. The single index method is a simplified method of the index model developed by Markowitz. This single index method explains the relationship between the return of each individual security and the market index return based on the observation of fluctuations in stock prices in line with the market price index. The research method used is qualitative method by analyzing the numbers or numerical in LQ45 stocks by visiting the official website of the Indonesia Stock Exchange (BEI), Yahoo Finance, and BI and the number of samples used is eight companies using purposive sampling. The results of this study indicate that there are five out of eight companies that have optimal portfolios. The optimal companies are PT Indotambangraya Megah Tbk (ITMG), PT Merdeka Copper Gold Tbk (MDKA), PT Indika Energy Tbk (INDY), PT Aneka Tambang Tbk (ANTM), and PT Adaro Energy Indonesia (ADRO) with an optimal portfolio return of 0.0463 or 4.63% and an optimal portfolio risk of 0.0073 or 0.73%. There are two optimization strategies in optimizing the optimal portfolio using the single index method, namely, active strategies and passive strategies, but these strategies can be selected depending on market conditions at that time.